Value of combined cardiopulmonary and echocardiography stress test to characterize the haemodynamic and metabolic responses of patients with heart failure and mid-range ejection fraction. (11th February 2019) - Pugliese, Nicola Riccardo; Fabiani, Iacopo; Santini, Claudia; Rovai, Ilaria; Pedrinelli, Roberto; Natali, Andrea; Dini, Frank L
Abstract: Aims: To characterize heart failure (HF) with mid-range ejection fraction (HFmrEF), combining cardiopulmonary exercise test, and exercise stress echocardiography. Methods and results: We studied 169 consecutive subjects (age 62.3 ± 11 years; 74% male): 30 healthy controls, 45 patients with HF and preserved EF (HFpEF), 40 HFmrEF, and 54 with HF and reduced EF (HFrEF). Left ventricular (LV) stroke volume (SV), EF, elastance, global longitudinal strain, E/E', oxygen consumption (VO2 ), and arterial-venous oxygen content difference (AVO2 diff) were measured in all exercise stages. HFmrEF revealed baseline features intermediate between HFrEF and HFpEF, except for B-type natriuretic peptide levels, which was similar to HFpEF and significantly lower than HFrEF. Peak VO2 was not significantly different between HF groups. HFrEF exhibited a significantly lower peak SV as compared to either HFpEF or HFmrEF (74.3 ± 21.8 mL vs. 88.0 ± 17.4 mL and 96.5 ± 25.1 mL; P < 0.01), whereas peak heart rate was not significantly different between HF groups. A significantly reduced AVO2 diff at peak exercise was apparent in HFpEF and HFmrEF (15.2 ± 3.3 mL/dL and 13.3 ± 4.2 mL/dL) vs. HFrEF (17.±6.6 mL/dL; P < 0.01), whereas no significant difference was reported between HFpEF and HFmrEF. Multivariate analysis in the overall population and all groups revealed peak parameters as independent predictors of peak VO2 ( R 2 = 0.90, P < 0.0001); AVO2 diff showed the largest standardized regression coefficient. Conclusion: In HFpEF and HFmrEF, effort intolerance is predominantly due to peripheral factors (AVO2 diff), whereas in HFrEF peak VO2 is restricted by low increases in SV. Individual therapy according to which component of VO2 is more impaired is advisable.